2020
DOI: 10.7202/1072592ar
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Risk of Harm to Self and Others: The Role of Sex and Polyvictimization

Abstract: Objectives: Research has shown that children who experience abuse and neglect are at much higher risk of experiencing negative outcomes such as physical and mental health problems, social skill deficits, and poor quality of life. The goal of this paper was to examine the relationship between polyvictimization and risk of harm to self and others, taking into account both age and sex differences. Methods: A total of 8980 participants (4156 with maltreatment history) were recruited from over 50 menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…The results reported herein also indicated an increase in girls witnessing domestic violence during the pandemic. Such exposure to violence has been known to be an important risk factor in NSSI (Armiento et al, 2016) as well as other mental health and relationship issues (Stewart et al, 2021; Stewart, Toohey, et al, 2020). To complicate things further, furloughs and stay-at-home orders might leave minimal opportunities for disclosure of child abuse and domestic violence and for health care workers and school personnel to accurately identify risk; consequently, it is likely that these rates are much higher than the results reported herein (Evans et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results reported herein also indicated an increase in girls witnessing domestic violence during the pandemic. Such exposure to violence has been known to be an important risk factor in NSSI (Armiento et al, 2016) as well as other mental health and relationship issues (Stewart et al, 2021; Stewart, Toohey, et al, 2020). To complicate things further, furloughs and stay-at-home orders might leave minimal opportunities for disclosure of child abuse and domestic violence and for health care workers and school personnel to accurately identify risk; consequently, it is likely that these rates are much higher than the results reported herein (Evans et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that children and youth with ID have verbal communication problems and may have difficulties reporting abuse or bullying. Extant literature has indicated that children and youth with ID are more likely to be victims of sexual abuse and bullying, but they may also be less likely to disclose such abuse, compared to non-ID counterparts (e.g., Lapshina & Stewart, 2018; McDonnell et al, 2019; McClean et al, 2017; Stewart, et al, 2020c).…”
Section: Discussionmentioning
confidence: 99%
“…These behaviors are consistent with Disinhibited Social Engagement Disorder (American Psychiatric Association, 2013; ZERO TO THREE, 2016), including precociousness (pseudomature interpersonal behaviors), and role-reversal behaviors (i.e., parentification;Hooper et al, 2008), consistent with anxious-preoccupied attachment (Bowlby, 1980;Lieberman & Zeanah, 1995). Such approachoriented behaviors exhibited by girls may be partially related to disproportionate rates of sexual abuse (Fallon et al, 2022;Finkelhor et al, 2015;Moody et al, 2018;Stewart et al, 2020;Wamser-Nanney & Cherry, 2018).…”
Section: Symptom-specific Gender Differences In Childrenmentioning
confidence: 99%